Occurrence and distribution of organic trace substances in waters from the Three Gorges Reservoir, China - Wolf, Anja; Bergmann, Axel; Wilken, Rolf-Dieter; Gao, Xu; Bi, Yonghong; Chen, Hao; Schüth, Christoph (Environmental science and pollution research international, 2013)
This study deals with the evaluation of water quality of the Three Gorges Reservoir (TGR) in order to assess its suitability as a raw water source for drinking water production. Therefore, water samples from (1) surface water, (2) tap water, and (3) wastewater treatment plant effluents were taken randomly by 2011–2012 in the area of the TGR and were analyzed for seven different organic contaminant groups (207 substances in total), applying nine different analytical methods. In the three sampled water sources, typical contaminant patterns were found, i.e., pesticides and polycyclic aromatic hydrocarbons (PAH) in surface water with concentrations of 0.020–3.5 μg/L and 0.004–0.12 μg/L, disinfection by-products in tap water with concentrations of 0.050–79 μg/L, and pharmaceuticals in wastewater treatment plant effluents with concentrations of 0.020–0.76 μg/L, respectively. The most frequently detected organic compounds in surface water (45 positives out of 57 samples) were the pyridine pesticides clopyralid and picloram. The concentrations might indicate that they are used on a regular basis and in conjunction in the area of the TGR. Three- and four-ring PAH were ubiquitously distributed, while the poorly soluble five- and six-ring members, perfluorinated compounds, polychlorinated biphenyls, and polybrominated diphenyl ethers, were below the detection limit. In general, the detected concentrations in TGR are in the same range or even lower compared to surface waters in western industrialized countries, although contaminant loads can still be high due to a high discharge. With the exception of the two pesticides, clopyralid and picloram, concentrations of the investigated organic pollutants in TGR meet the limits of the Chinese Standards for Drinking Water Quality GB 5749 (Ministry of Health of China and Standardization Administration of China 2006 ) and the European Union (EU) Council Directive 98/83/EC on the quality of water intended for human consumption (The Council of the European Union 1998 ), or rather, the EU Directive on environmental quality standards in the field of water policy (The European Parliament and The Council of the European Union 2008 ). Therefore, the suggested use of surface water from TGR for drinking water purposes is a valid option. Current treatment methods, however, do not seem to be efficient since organic pollutants were detected in significant concentrations in purified tap water.